Near-Infrared Spectroscopy Assessments of Regional Cerebral Oxygen Saturation for the Prediction of Clinical Outcomes in Patients With Cardiac Arrest: A Review of Clinical Impact, Evolution, and Future Directions - Takegawa, Ryosuke; Hayashida, Kei; Rolston, Daniel M.; Li, Timmy; Miyara, Santiago J.; Ohnishi, Mitsuo; Shiozaki, Tadahiko; Becker, Lance B. (Frontiers in Medicine, 2020)
Despite three decades of advancements in cardiopulmonary resuscitation (CPR) methods and post-resuscitation care, neurological prognosis remains poor among survivors of out-of-hospital cardiac arrest, and there are no reliable methods for predicting neurological outcomes in patients with cardiac arrest (CA). Adopting more effective methods of neurological monitoring may aid in improving neurological outcomes and optimizing therapeutic interventions for each patient. In the present review, we summarize the development, evolution, and potential application of near-infrared spectroscopy (NIRS) in adults with CA, highlighting the clinical relevance of NIRS brain monitoring as a predictive tool in both pre-hospital and in-hospital settings. Several clinical studies have reported an association between various NIRS oximetry measurements and CA outcomes, suggesting that NIRS monitoring can be integrated into standardized CPR protocols, which may improve outcomes among patients with CA. However, no studies have established acceptable regional cerebral oxygen saturation cut-off values for differentiating patient groups based on return of spontaneous circulation status and neurological outcomes. Furthermore, the point at which resuscitation efforts can be considered futile remains to be determined. Further large-scale randomized controlled trials are required to evaluate the impact of NIRS monitoring on survival and neurological recovery following CA.